POTENSI PRODUKSI ARANG DARI HUT AN RAKY AT DESA BANGUNJIWO, KECAMATAN KASIHAN, BANTUL, DAERAH ISTIMEW A YOGYAKART A - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Asam jawa (Tamarindus indica) and mahoni (Swietenia macrophylla) which predominantly grow on the community forests of Bangunjiwo Village are an ideal candidate as raw matterial of charchoal roduction because they're hard wood makes good quality charchoal and income from its charchoal are an tractive source of supplemental revenue. Information on its charchoal production are needed, but this information is c:urrently lacking. The potential of charcoal production of woody perennial in the community forests were estimated by developing allometric equations for standing trees. To establish the equations 30 sample logs of tamarind and 29 sample logs of mahoni were made charcoal by traditional kiln to determine the relationships between the mechantable timber volume/log (Vkp) and its charcoal production (Pa). The raw material of charcoal production from the merchantable timber volume in the community forests was the ligneous material. contained in the bole and branches which both with a diameter of at least 7 em. The results showed that the merchantable timber volume was strongly related to the charcoal production (tamarind: Pa = 185.6180 (Vkpf0,9455, n = 30, r²